A Comparative Study of the Antioxidant Activities of Black Goji Berry (Lycium Ruthenicum) and Chinese Jujube (Zizyphus Jujube Mill.), and their Combination - Rastiti, Ida Ayu Anom; Strisanti, Ida Ayu Suptika; Sintyadewi, Putu Rima (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Oxidative stress, which arises from an imbalance between free radicals and the body’s antioxidant defences, is a major factor in the development of degenerative diseases, making the search for natural antioxidants an important area of research. Black goji berry (Lycium ruthenicum) is known to be rich in anthocyanins and polyphenols, while Chinese jujube (Ziziphus jujuba) contains high levels of vitamin C, flavonoids, and polysaccharides; both have been traditionally used in herbal medicine and are considered promising natural antioxidants. This research is the first study that examines the synergistic antioxidant effect of black goji berry and Chinese jujube. An experimental laboratory study was conducted with five treatment groups consisting of Chinese jujube (100%); black goji berry (100%); black goji berry 75% : Chinese jujube 25%; black goji berry 25% : Chinese jujube 75%; and black goji berry 50% : Chinese jujube 50%. Infusion samples were analyzed for antioxidant activity, and data were further analyzed statistically using one-way ANOVA followed by Tukey’s post hoc test. The results demonstrated significant differences in antioxidant activity among treatments (p < 0.05). Chinese jujube exhibited the weakest activity with an IC50 value of 35,695.24 ppm, while the 50:50 combination of black goji berry and Chinese jujube showed the strongest activity with an IC50 of 1,605.07 ppm. Groups containing black goji berry, either alone or in combination, consistently displayed better radical scavenging activity than Chinese jujube alone. These findings indicate that both black goji berry and Chinese jujube possess antioxidant potential; however, their combination, particularly in equal proportions, enhances this effect, suggesting a synergistic interaction. The results support the potential of these herbal mixtures as a complementary source of antioxidants to mitigate oxidative stress and prevent chronic diseases. They also highlight the value of studying plant combinations rather than single extracts.